Penerapan Konseling Individual Untuk Remaja Dengan Self-Esteem Rendah di Sekolah Menengah Pertama Kota Palangka Raya - Kamila, Bina Aulia; Mulyaningsih, Dian; Erawati, Desi (Institut Agama Islam Sumatera Barat, 2024)
This study aims to evaluate the effectiveness of individual counseling interventions using a Cognitive Behavior Therapy (CBT) approach in improving the Self-Esteem and social skills of adolescents who experience low Self-Esteem. The results of the study showed that through four stages of meetings, the intervention succeeded in improving client behavior significantly. The initial stage shows that the client is not yet fully aware of the problem of low Self-Esteem, but with the counselor's approach to building a good relationship, the client begins to consider making changes. The final stage shows significant changes in the client's social skills and self-confidence through positive interactions with friends. During the counseling process, counselors also utilize verse 119 of Surah An-Nisa as a warning against negative thoughts and self-defeating behavior. This research shows that individual counseling interventions with a CBT approach have great potential in improving the Self-Esteem and social skills of adolescents who experience low Self-Esteem, although further research is needed to measure the long-term effects.